Comparative study of Ni loading methods towards superior CO2 conversion over Ni/SBA-15 - Syahida Nasuha, Bukhari; C. C., Chong; Herma Dina, Setiabudi; N., Ainirazali; M. A., A. Aziz; L. P., Teh; N. H. R., Annuar (2018)
A series of Ni/SBA-15 catalysts were successfully synthesized via conventional wet impregnation method (C-IM), P123-assisted impregnation method (P123-IM) and ultrasonic-assisted impregnation technique (US-IM) methods. The obtained results confirmed that the impregnation methods significantly influenced the physio-chemical properties of Ni/SBA-15 catalysts, which subsequently influenced the catalytic performances of catalysts. The catalytic performance of catalysts followed the order of Ni/SBA-15(P123-IM) > Ni/SBA-15(US-IM) > Ni/SBA-15(C-IM), indicating the superior performance of Ni/SBA-15(P123-IM) towards CO2 methanation (CO2 conv.: 91.1 % , CH4 selec.: 97.7 %) and CO2 dry reforming (CO2 conv.: 82.6 % , H2/CO: 1.23). An excellent catalytic performance of Ni/SBA-15(P123-IM) owing to its favorable textural properties; homogenous Ni dispersion, smaller NiO crystallite size (12.1 nm), and higher concentration of metal-support interaction. P123-IM method successfully synthesized favorable Ni/SBA-15 for superior CO2 conversion.